Biochemical Flavour Parameters of Milk in Early Lactation - Bayril, T.; Cimen, M.; Tekelioglu, O. (Asian Journal of Chemistry, 2010)
This research was aimed to investigate the biochemical flavour parameters of milk by machine milking in early lactation period. In the experiment, milk samples from 50 Holstein cows were used. Cows were fed high-energy concentrate diet (140 g crude protein and 10.3 metabolizable energy MJ/d). The data was collected from DIMES Company during July month. The milk fat rates were lower (p < 0.05) for cows in first and second weeks than last week. Cows were shown to be more sensitive to milk fat syndrome for first and second weeks. A decrease in milk fat percentage for summer period (2.3-2.6 %) can directly lead to taste loss. There were statistically no significant differences between the weeks for milk acidity (sH and pH) values during July. The milk acidity values (sH and pH) during July were tolerable for desired taste and favourable for consumer preference.